Kesan teaching games for understanding (TGFU) terhadap hasil pembelajaran dalam permainan mini hoki / Wee Akina Sia Seng Lee - Wee Akina, Sia Seng Lee (2016)
This study was conducted to examine the effects of Teaching Games for Understanding (TGFU) towards form four pupils’ learning outcomes (Psychomotor: total game performance, execution of hockey dribbling skills; Cognitive: tactical understanding and decision making; Affective: intrinsic motivation and self-confidence) in mini hockey games. A quasi experimental design with pretest and posttest was used in this study. A total of 259 form four pupils’ (boys and girls) aged 16 years old were selected for this study based on intact sampling method from two secondary schools in Segamat, Johor. The control groups consisted of (boys=60, girls=70) and treatment groups with (boys=60, girls=69). The control groups underwent the Traditional Teaching, while the treatment groups underwent intervention in the form of TGFU in mini hockey games within physical education classes conducted twice a week for four weeks. The instruments’ of Game Performance Assessment Instrument (GPAI) were used to see the effects of the learning outcomes (Psychomotor: total game performance, execution of hockey dribbling skills; Cognitive: tactical understanding, decision making), Situational Motivational Scale Instrument (SIMS) and State Sport-Confidence Instrument (SSCI) (Affective: intrinsic motivation and self-confidence) among form four pupils’ in a mini hockey games. After four weeks, analysis of ANCOVA indicated that the treatment groups (TGFU) were significant in learning outcomes [Psychomotor: school boys’ total game performance with F(1, 117)= 348.63, ES= 0.75;. school girls’ total game performance with F(1, 136)= 95.09, ES= 0.41; Cognitive: school boys’ tactical understanding with F(1, 117)= 313.37, ES= 0.73, school girls’ tactical understanding with F(1, 136)= 92.62, ES= 0.41; Affective: school boys’ identified regulation domain with F(1, 117)= 0.05, ES= 0.83, school girls’ intrinsic motivation domain with F(1, 136)= 56.36, ES= 0.29, school girls’ identified regulation domain with F(1, 136)= 7.45, ES= 0.05, school girls’ external regulation domain with F(1, 136)= 7.30, ES= 0.05] and school girls’ self-confidence with F(1, 136)= 74.40, ES= 0.35, p <. 05 in the mini hockey games compared to the control groups (Traditional Teaching). Independent t-test showed the school boys in the treatment groups (TGFU) had significant improvement than the control groups (Traditional Teaching) for the intrinsic motivation domain with t(2, 118)= -6.26, p <. 05 in the mini hockey games. Mann Whitney U test indicated a significant improvement in learning outcomes [Psychomotor: school girls’ hockey dribbling skills with U= 1138.50, z= -5.70, r= 0.04; Cognitive: school boys’ decision making with U= 450.00, z= -7.66, r= 0.06, school girls’ decision making with U= 1167.00, z= -5.58, r= 0.04] and school boys’ self-confidence with U= 428.50, z= -7.22, r= 0.06, p <. 05 in mini hockey games which showed the treatment groups (TGFU) were better than control groups (Traditional Teaching). This indicates that TGFU within physical education class conducted twice a week for four weeks significantly improved the learning outcome among form four school pupils’ in mini hockey games in two secondary schools in Segamat, Johor. The significance of the study in terms of implications to theory and practice can provide the latest information to the Physical Education teachers and Physical Education curriculum developers to suggest TGFU as a vital part of teaching method for Form Four’s Physical Education Curriculum in hockey games.